EFIKASI PROPOLIS LEBAH Trigona sp. SEBAGAI BAHAN EDIBLE COATING UNTUK PERLINDUNGAN PASCA PANEN BUAH PISANG AMBON LUMUT (Musa acuminata L.) - Imam Fathurrahman; Ramadhani Eka Putra (JURNAL AGROTEKNOLOGI, 2016)
This study aimed to determine the efficiency of the use of propolis as a biocoating for post-harvest bananas in order to extend shelf life. This study used local banana that typical in Indonesia, Moss banana (Musa acuminata) and the propolis bee Trigona laeviceps, which is also produced by local agriculture, with a concentration of application 5%, 10%, 15%, coating using 70% ethanol as a positive control, and bananas without coating as a negative control. Observation parameters that measured are weight loss, pulp to peel ratio, size, color, fruit temperature, cell death, fruit firmness, total soluble solid (TSS), sucrose content, vitamin C, and potassium content on days 0, 3, 6, 9, 12, 15, 18 and 21 after coating. The results showed that coating using 5% propolis significantly extend the shelf life compared to the control by slowing the increase in fruit maturity index (color), weight loss, size loss, pulp to peel ratio, fruit temperature, pulp softening, and increased levels of vitamin C. Treatment process itself does not have a significant effect on changes in the value of TSS and sucrose during the storage period.Keywords: propolis, moss banana, post-harvest protection.